Nanoliposome C6‐Ceramide in combination with anti‐CTLA4 antibody improves anti‐tumor immunity in hepatocellular cancer. Issue 4 (16th March 2022) - Qi, Xiaoqiang; Wu, Feng; Kim, Sung Hoon; Kaifi, Jussuf T.; Kimchi, Eric T.; Snyder, Helena; Illendula, Anuradha; Fox, Todd; Kester, Mark; Staveley‐O'Carroll, Kevin F.; Li, Guangfu
Abstract: Combination therapy represents an effective therapeutic approach to overcome hepatocellular cancer (HCC) resistance to immune checkpoint blockade (ICB). Based upon previous work demonstrating that nanoliposome C6‐ceramide (LipC6) not only induces HCC apoptosis but also prevents HCC‐induced immune tolerance, we now investigate the potential of LipC6 in combination with ICB in HCC treatment. We generated orthotopic HCC‐bearing mice, which have typical features in common with human patients, and then treated them with LipC6 in combination with the antibodies (Abs) for programmed cell death protein 1 (PD‐1) or cytotoxic T‐lymphocyte antigen 4 (CTLA4). The tumor growth was monitored by magnetic resonance imaging (MRI) and the intrahepatic immune profiles were checked by flow cytometry in response to the treatments. Realtime PCR (qPCR) was used to detect the expression of target genes. The results show that LipC6 in combination with anti‐CTLA4 Ab, but not anti‐PD‐1 Ab, significantly slowed tumor growth, enhanced tumor‐infiltrating CD8 + T cells, and suppressed tumor‐resident CD4 + CD25 + FoxP3 + Tregs. Further molecular investigation indicates that the combinational treatment suppressed transcriptional factor Krüppel‐like Factor 2 (KLF2), forkhead box protein P3 (FoxP3), and CTLA4. Our studies suggest that LipC6 in combination with anti‐CTLA4 Ab represents a novel therapeutic approach with significant potential in activating anti‐HCC immune response and suppressing HCC growth.